Биопотенциал функционирующей мышцы, гиперсинхронизация и тип электромиограммы при спастическом синдроме миелодисплазии - Сиротюк, М.В. (Таврический медико-биологический вестник, 2014)
У роботі наведені дані дослідження 87 електроміограму м’язів нижніх кінцівок у дітей з мієлодисплазією. Аналіз електроміограму включав в себе характеристику биопотенциала і гіперсінхронізаціі функціонуючої м’язи проксимального і дистального відділу нижньої кінцівки, тип ЕМГ. Порівняльні дані відображають переважно дистальний тип ураження при міелодисплазії на тлі «мозаїчності» дисфункції нервово-м’язового апарату. Зроблено висновок, що електроміографічні дані при спастичному синдромі вказують на дифузний (нерівномірний) характер мієлодиспластичного процесу, що для нього притаманне і відрізняє від спастичних форм дитячого церебрального паралічу. This paper presents the data of a study of 87 electromyograms of the lower limb muscles in 56 children with myelodysplasia. The electromyogram analysis includes biocapacity characterization and functioning muscle hypersynchronization of the proximal and distal lower limb, EMG type. Comparative figures reflect mainly the distal type of lesion in myelodysplasia on the background of the “mosaic” dysfunction neuro-muscular system. It has been concluded that the electromyographic data on the spastic syndrome indicate a diffuse (uneven) character of the myelodysplastic process that is inherent to it and differs it from the spastic form of cerebral palsy.